Analisys of The Effectiveness of The Utilization of Electronic Government On State-Owned Enterprises - Andi Rahmatiah (Universitas Negeri Makassar, 2021)
The use of electronic government (e-gov) of face and finger access control has been implemented at PT. PLN Tello Sector Makassar City and is expected to be able to streamline employee performance. The purpose of this study, is to analyze the effectiveness of the use of face and finger access control at PT. PLN Tello Sector Makassar City. This research method uses quantitative research types with quantitative descriptive research types. Data collection techniques using questionnaires in the form of a checklist and using descriptive analysis techniques. The results showed that the effectiveness of the use of face and finger access control at PT. PLN Tello Sector Makassar City is in quite good category, based on the analysis of target achievement indicators, adaptability, job satisfaction, and responsibility.